A range‐expanding butterfly is susceptible to cold and long winters but shows no signs of local adaptation to winter conditions - Ittonen, Mats; Roberts, Kevin T.; Lehmann, Philipp; Gotthard, Karl (Functional ecology, 2023)
Numerous species shift or expand their ranges poleward in response to climate change. Even when expanding species follow their climatic niches, expanding range margin populations are likely to face unfamiliar environmental conditions and thus natural selection for local adaptation. The wall brown butterfly (Lasiommata megera) has expanded northward in Sweden in the years 2000–2020, most likely as a result of climate change, and has previously been shown to have evolved local adaptations to northern daylength conditions. This evolution has occurred despite hypothesised genetic constraints to adaptation at range margins. We studied local adaptation to winter conditions in four of the previously‐studied L. megera populations, using a common garden laboratory experiment with a warm and short, an intermediate, and a cold and long winter treatment. We compared the winter and post‐winter survival of caterpillars from two southern core range and two northern range margin populations in Sweden. During the experiment, we measured metabolic rates of a subset of diapausing caterpillars to test whether populations differ in metabolic suppression during diapause. Further, we measured supercooling points, which reflect lower lethal temperature in L. megera, of the same subset of caterpillars. We also compared supercooling points between L. megera and three closely related species with more northern distributions. Few individuals survived the coldest treatment all the way to successful adult emergence, so L. megera seems susceptible to cold winters. Individuals of northern descent did not survive cold winters any better than individuals from southern populations. Similarly, there were no signs of local adaptation in metabolic rates or supercooling points. The comparison among species did not reveal any clear relationship between geographical distribution and supercooling point. Although northern winters probably exert strong selection on L. megera, we provide comprehensive evidence for the lack of local adaptation to winter conditions. This contrasts with the previous finding of quickly evolved local adaptation in diapause timing, highlighting the need to consider how traits associated with different seasons differ in how they may evolve and facilitate climate change‐induced range expansions. Read the free Plain Language Summary for this article on the Journal blog. Sammanfattning Som en följd av klimatförändringar förflyttar sig eller expanderar många arter mot polerna. Även om en sådan art bara följer sin klimatnisch, är det sannolikt att populationer nära kanten av artens utbredningsområde utsätts för främmande miljöförhållanden och därmed naturligt urval för lokal anpassning. Svingelgräsfjärilen (Lasiommata megera), som – sannolikt till följd av klimatförändringar – expanderat norrut i Sverige under åren 2000–2020, har tidigare visats ha anpassat sig lokalt till nordliga dagslängdsförhållanden. Denna evolution har skett trots hypoteser om att genetiska begränsningar kan hindra evolution vid utbredningskanter. Vi studerade lokal anpassning till olika vinterförhållanden i fyra av de tidigare studerade svingelgräsfjärilspopulationerna. Vi lät larver från olika populationer övervintra i tre olika experimentella vinterförhållanden: en varm och kort, en intermediär och en kall och lång vinter. Vi jämförde överlevnaden av larver från två sydsvenska populationer och två populationer vid artens norra utbredningskant i Sverige. Under experimentets lopp mätte vi ämnesomsättningen hos en del larver för att testa huruvida populationer skiljer sig i hur starkt nedsatt ämnesomsättning diapauserande larver har. Utöver det mätte vi, med samma individer, vid vilken temperatur larvers underkylda kroppsvätskor fryser. Detta reflekterar de lägsta temperaturerna som svingelgräsfjärilslarver kan överleva. Dessutom jämförde vi svingelgräsfjärilens underkylningsförmåga med tre nära besläktade arter med mer nordliga utbredningsområden. Få individer både överlevde den kallaste behandlingen och utvecklades till friska vuxna fjärilar, så svingelgräsfjärilen verkar känslig för kalla vintrar. Individer från nordliga populationer klarade inte vintern bättre än de sydliga. Likaså visar våra resultat inga tecken på lokal anpassning i underkylningsförmåga eller nedsättning av ämnesomsättningen. Jämförelsen mellan arter visade inget tydligt förhållande mellan arters utbredningsområden och underkylningsförmåga. Trots att nordliga vintrar sannolikt medför starkt naturligt urval hos svingelgräsfjärilen, presenterar vi flera belägg för avsaknaden av lokal anpassning till vinterförhållanden. Detta är i motsats till den tidigare upptäckten av snabb evolution av lokal anpassning i diapaustajmning och påvisar att olika årstidsberoende egenskaper kan skilja sig i hur de genom evolution kan utvecklas och främja klimatdrivna utbredningsförändringar. Read the free Plain Language Summary for this article on the Journal blog.